Impact of training and development on employee performance in the local government of Ghana (a case study of Nsawam Adoagyiri municipal assembly). - Tackie, Yarboi Andrews Ofoli (KNUST, 2025)
This Thesis Is Submitted In Partial Fulfilment Of The Requirement For Award Of The Degree In Master Of Public Administration.